Peningkatan Proses Dan Hasil Belajar Bahasa Indonesia Menggunakan Model Pembelajaran Think Talk Write Kelas V SD Negeri 102/II Sungai Kerjan - Della Palianti; Aprizan Aprizan; Dhini Mufti (Journal of Innovative and Creativity (Joecy), 2026)
This study was motivated by the low learning process and learning outcomes in Indonesian language among students. The purpose of this study was to describe the improvement of the learning process and learning outcomes in Indonesian language through the implementation of the Think Talk Write learning model for Grade V students of SD Negeri 102/II Sungai Kerjan. The research employed Classroom Action Research (CAR), which was conducted in two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The research subjects were 20 fifth-grade students of SD Negeri 102/II Sungai Kerjan. The research data consisted of qualitative and quantitative data. The qualitative data were obtained through observation sheets of teacher and students' activities as well as documentation during the learning process. Meanwhile, the quantitative data were obtained from students' learning achievement tests administered at the end of each cycle. The results showed that the implementation of the Think Talk Write learning model improved both the learning process and the learning outcomes in Indonesian language. The improvement in the learning process was reflected in the increased quality of teacher and student activities in each cycle, while the improvement in learning outcomes was indicated by the increase in students' learning mastery from 60% in Cycle I to 75% in Cycle II. Therefore, the research success indicators were achieved. It can be concluded that the Think Talk Write learning model is effective in improving the learning process and learning outcomes in Indonesian language for Grade V students of SD Negeri 102/II Sungai Kerjan.